Molecular evidence-based first DNA barcoding of miniature freshwater fish in Bangka Island, Indonesia - ABU BAKAR SAMBAH; FITRI SIL VALEN; DIAN SAMITRA; UUN YANUHAR; AHMAD SYAZNI KAMARUDIN; AKHMAD TAUFIQ MUKTI; DITA WISUDYAWATI; OCHEI MICHAEL CHUKWUEMEKA; VERYL HASAN (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Sambah AB, Valen FS, Samitra D, Yanuhar U, Kamarudin AS, Mukti AT, Wisudyawati D, Chukwuemeka OM, Hasan V. 2025. Molecular evidence-based first DNA barcoding of miniature freshwater fish in Bangka Island, Indonesia. Biodiversitas 26: 5476-5484. Paedocypris spp., among the world’s smallest vertebrates, inhabit Southeast Asian peat swamp ecosystems but remain taxonomically challenging due to their miniature body size and cryptic morphology. These habitats are simultaneously among the most threatened freshwater ecosystems. This study presents the first DNA barcoding assessment of Paedocypris from Bangka Island, Indonesia, undertaken to resolve its species identity and phylogenetic placement. Specimens were collected from blackwater peat swamps, and the mitochondrial cytochrome C Oxidase subunit I (COI) gene was sequenced. BLAST analysis revealed 96% similarity to both Paedocypris progenetica (AP011287.1) and Paedocypris micromegethes (NC_051487.1), but only 89% to Paedocypris carbunculus (NC_051488.1). Phylogenetic reconstruction clustered the Bangka specimens with P. micromegethes (bootstrap = 85) on a distinct lineage, while pairwise genetic distance analysis indicated 4.18% divergence. This exceeds conventional intraspecific thresholds in fishes, suggesting potential species-level differentiation, possibly driven by geographic isolation, ecological adaptation, or cryptic speciation. Beyond its systematic significance, this finding extends the known distribution of Paedocypris beyond Borneo, Sumatra, and Peninsular Malaysia, contributing to Sundaland biogeography and understanding of evolutionary patterns in miniature fishes. The conservation implications are profound: Bangka’s peat swamp ecosystems are undergoing rapid degradation due to tin mining, peatland drainage, and large-scale conversion to oil palm plantations. These pressures erode the ecological integrity of blackwater habitats, threatening the persistence of Paedocypris and other specialized endemics. This study underscores the urgency of targeted habitat protection, ecological restoration, and sustainable land-use planning to safeguard these fragile ecosystems. Integrating molecular evidence into conservation strategies is vital not only for the survival of Paedocypris but also for maintaining freshwater biodiversity and ecosystem resilience across the region.